A congruence perspective on how human and social capital affect learning capability and innovation - Sun, Rui; Li, Shuwen; Liu, Wei (PloS one, 2020)
Human capital and social capital are vital for sustainable development of organization, but existing studies are inadequate to explore the synergistic effect of them on organizational behaviors or organizational outcomes. The research employed multiple-source questionnaire to collect data of more than 400 R&D firms from leaders and corresponding employees in Chinese context. Bootstrapping method and response surface were used to analyze the associations between all the parameters. The results showed that: (1) in the case of the in-congruence between human capital and social capital, learning capability of R&D firms is at highest level when human capital is at low level and social capital is at high level; (2) learning capability partially mediates the impact of human capital and social capital on innovation performance; (3) environmental dynamism and environmental competitiveness have a joint moderating effect on the relationship between learning capability and innovation performance.